Determinants of willingness-to-pay for sustainable wine: Evidence from experimental auctions - Riccardo Vecchio (Wine Economics and Policy, 2013)
The current paper explored young adult wine drinkers' willingness to pay (WTP) for three sustainable wines through Vickrey fifth-price full bidding auctions. In order to investigate factors affecting WTP the study compared the bid functions estimated with Tobit models and the premium functions estimated with ordinary least squares (OLS). The econometric results reveal that female and older respondents tend to bid higher for sustainable wines. Moreover, knowledge of specific claims increased price premiums. Our findings have significant marketing and policy implications for the promotion of sustainable wines among young adults.
Keywords: 330; Experimental auctions; Sustainable wine; Willingness-to-pay